Overcoming Mutual Estrangement? - Margot Renard (Tahiti)
Despite their relevance in art history, comics have been largely overlooked in the research field. This article builds on recent scholarship that has addressed their historical marginalization in the field by focusing on Jean Dytar’s graphic novel #J’Accuse…! (2021). The graphic novel revisits the Dreyfus Affair, a pivotal event in nineteenth-century France that marked the rise of mass media by generating an unprecedented media coverage. Drawing from art history and media archaeology, the article explores how Dytar’s narrative intertwines past and present to propose a graphic theory of media and examine the notion of “historical event.”